1996
DOI: 10.3109/03008209609021495
|View full text |Cite
|
Sign up to set email alerts
|

Topically Applied Halofuginone, An Inhibitor of Collagen Type I Transcription, Reduces Peritendinous Fibrous Adhesions Following Surgery

Abstract: To test in vivo the effect of previously observed inhibition of collagen type I transcription by the plant alkaloid Halofuginone, deep flexor tendons of 12 chickens were severed and sutured, and Halofuginone was applied topically at the site of surgery. Intact tendons, and severed but untreated tendons served as controls. The effect of the treatment was assessed by histological, biochemical, and biomechanical examinations of the operated and intact tendons three weeks after surgery. The results indicated an al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
20
0

Year Published

2000
2000
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(20 citation statements)
references
References 13 publications
0
20
0
Order By: Relevance
“…Recently, halofuginone has been identified as a specific inhibitor of collagen type I gene expression (5,25). The rediscovery of halofuginone has led to intensive preclinical studies and rapid development of the drug for the control of many diseases involved in excessive collagen synthesis, such as pulmonary fibrosis (21), liver cirrhosis (24), peritendinous fibrous adhesions after surgery (22), wound repair (1), and injury-induced arterial intimal hyperplasia (18). A phase I clinical trial of halofuginone for the treatment of scleroderma is under way, and a phase II clinical trial of Tempostatin (halofuginone hydrobromide) for the treatment of recurring bladder carcinoma has just started in the United Kingdom.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, halofuginone has been identified as a specific inhibitor of collagen type I gene expression (5,25). The rediscovery of halofuginone has led to intensive preclinical studies and rapid development of the drug for the control of many diseases involved in excessive collagen synthesis, such as pulmonary fibrosis (21), liver cirrhosis (24), peritendinous fibrous adhesions after surgery (22), wound repair (1), and injury-induced arterial intimal hyperplasia (18). A phase I clinical trial of halofuginone for the treatment of scleroderma is under way, and a phase II clinical trial of Tempostatin (halofuginone hydrobromide) for the treatment of recurring bladder carcinoma has just started in the United Kingdom.…”
Section: Discussionmentioning
confidence: 99%
“…28 In animal models in which fibrosis was induced, halofuginone prevented the increase in collagen synthesis and collagen ␣1(I) gene expression. These models included mice afflicted with cGvHD, 29 rats with pulmonary fibrosis after bleomycin treatment, 30 and rats developing adhesions after surgery in tendons, 31 the abdomen, 32 and uterine horns. 33 In liver, halofuginone prevented collagen type I gene expression in dimethylnitrosamine-induced cirrhosis in rats.…”
mentioning
confidence: 99%
“…HF has been reported to reduce Wbrosis after bleomycininduced pulmonary Wbrosis [9], to improve Wbrosis after dimethylnitrosamine-induced liver cirrhosis in rats [7], to reduce postoperative Wbrous tendinous adhesions in chickens [10], to prevent postoperative intra-abdominal adhesions [11]. Our recent study showed that HF decreases Wbrosis/scar tissue formation secondary to experimentally induced subglottic trauma in the rat model [12].…”
Section: Discussionmentioning
confidence: 94%